Clinical and genetic analysis of methylmalonic aciduria in 60 patients from Southern China: a single center retrospective study - Hiba Abid; Areeba Abid; Sarah Sohail; Sara Jawaid (Orphanet Journal of Rare Diseases)
Abstract We read with interest the recent publication on methylmalonic aciduria (MMA) and commend the authors for their outstanding contribution. This letter aims to further build upon their work by emphasizing additional aspects to enhance clinical relevance and diagnostic precision. We highlight the variability in serum MMA levels due to dietary intake, renal function, and external factors, advocating for the integration of supplementary diagnostic tools, such as the 1–13 C-propionate oxidation breath test, alongside biomarkers like fibroblast growth factor 21, growth differentiation factor 15, and lipocalin-2, to improve diagnostic accuracy. Additionally, we discuss the limitations of first-tier newborn screening tests due to high false positive rates and recommend second-tier testing using liquid chromatography coupled with tandem mass spectrometry to increase specificity and reduce false positives. Moreover, we address the underestimation of liver dysfunction in MMA patients, noting the need for longitudinal follow-up to capture the progression of liver function abnormalities. This critique is intended to constructively expand the authors’ findings and underscore the importance of a comprehensive diagnostic and management approach to MMA, ultimately improving patient outcomes.